Cisatracurium Retards Cell Migration and Invasion Upon Upregulation of p53 and Inhibits the Aggressiveness of Colorectal Cancer - Yabasin, Iddrisu B.; Sanches, Jaceline G. P.; Ibrahim, Mohammed M.; Huidan, Jin; Williams, Walana; Lu, Zhi-Li; Wen, Qingping (Frontiers in Physiology, 2018)
Colorectal cancer (CRC) is reported to be the third and fourth most diagnosed and cause of cancer associated deaths respectively. In 2012 for instance, about 1.4 million new cases were reported, and approximately 700,000 deaths recorded. Survival from colorectal cancer is dependent on the stage at it is diagnosed and appropriate surgical intervention. Cisatracurium is widely used for skeletal muscle relaxation during abdominal surgeries, including bowel and colon surgeries. Recent studies reported that cisatracurium inhibits progression of human cancer cells, however, the mechanisms leading to the inhibition are yet to be completely understood. To elucidate mechanisms resulting particularly in tumor cell growth and metastasis, we developed ex vivo and in iv vivo xenograft models of colorectal cancer. Cisatracurium resulted in over-expression of p53 and its down-stream genes and proteins known to regulate proliferation and metastasis in vitro and in vivo. Genomic analyses of CRC following cisatracurium treatment revealed moderate to high DNA damage. Functional analyses demonstrated significant tumor cells growth regression, as well as repression of migration and invasion. Importantly, cisatracurium increased E-Cadherin and CALD-1 but decreased SNAI-1 and SLUG levels both in vitro and in vivo. Together, these data suggest that elevation of p53 upon cisatracurium-induced genomic injury, represent a potential mechanism by which cisatracurium result in the suppression of CRC progression and metastasis.